2017
DOI: 10.1093/jxb/erx280
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol is produced from starch and polar lipids in the green alga Dunaliella tertiolecta

Abstract: The major carbon source for triacylglycerol (TAG) biosynthesis in Dunaliella is starch, whose production precedes that of TAG under nitrogen deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 55 publications
3
38
0
1
Order By: Relevance
“…However, the higher level of intracellular ROS induced by EL and N-starvation limited the precursors of polysaccharide and enhanced lipid accumulation. The finding that C. reinhardtii converted starch into lipid was also consistent with reported researches [ 94 96 ], which might suggest that starch served as the major carbon source for lipid production. Consequently, the carbon partitioning was first oriented to starch as the stored substance in response to N-starvation.…”
Section: Approaches For Enhancing Biomass and Product Accumulation Masupporting
confidence: 92%
“…However, the higher level of intracellular ROS induced by EL and N-starvation limited the precursors of polysaccharide and enhanced lipid accumulation. The finding that C. reinhardtii converted starch into lipid was also consistent with reported researches [ 94 96 ], which might suggest that starch served as the major carbon source for lipid production. Consequently, the carbon partitioning was first oriented to starch as the stored substance in response to N-starvation.…”
Section: Approaches For Enhancing Biomass and Product Accumulation Masupporting
confidence: 92%
“…Under stress conditions such as nitrogen (N) deprivation, microalgae synthesized large amounts of TAG (Hu et al ; Slocombe et al ). Pick and Avidan found that TAG accumulated during N deprivation in D. tertiolecta , and around two‐thirds of the carbon in total TAG originated from starch, one‐third was made de novo by CO 2 assimilation (Pick and Avidan ). In this study, the N in culture medium was measured on the seventh day, and no N starvation was observed (Table S3), indicating that the accumulation of neutral lipid was induced by high light instead of N deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the neutral lipids in D. tertiolecta are mainly composed of TAGs. Supportively, (Rabbani, Beyer, Von Lintig, Hugueney, & Kleinig, 1998) reported that TAGs are the main component of neutral lipid bodies in Dunaliellabardawil.More recently, (Pick & Avidan, 2017) reported that polar lipids and starch made by photosynthetic carbon assimilation at the early stages of N deprivation might be utilized for the synthesis of TAG in D. tertiolecta.…”
Section: Dissection Of Triacylglycerol Productionmentioning
confidence: 99%